(untitled) (REMUNOM, 2025)
The advancement of artificial intelligence (AI) in mathematics education has generated discussions about its impacts on teaching practices and student learning. This article investigates the effects of AI in mathematics education, highlighting the personalization of teaching, automation of assessments, and challenges related to technological dependency and the devaluation of the teacher’s role. The research is based on a recent literature review and emphasizes the need for a balanced implementation of AI in mathematics education to avoid harmful effects, such as the reduction of critical thinking and the increase in educational inequalities.